Genetic diversity analysis in soybean (Glycine max L.): Genetic diversity analysis in soybean (Glycine max L.) - V R GHUGE,; D V SURNAR,; R S JADHAV,; B S RANDHAVE,; N R THAKUR, (Journal of Oilseeds Research, 2023)
Using Mahalanobis D2 Statistics, genetic diversity research was carried out on 321 different genotypes of Soybean (Glycine max L.) at All India Coordinated Research Project on Soybean, Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani, Maharashtra. Total 321 genotypes were classified into ten clusters based on D2 values. Cluster II, cluster VII, cluster VI, cluster V and cluster IX had 74, 15, 9, 3 and 2 genotypes, respectively, whereas, cluster I had the maximum genotypes of 214. One genotype was present in clusters III, IV, VIII and X. Cluster VII (1230.69) had the greatest intra-cluster distance, followed by Cluster VI (1104.13), Cluster II (604.39), Cluster I (478.57), Cluster IX (209.08) and Cluster V (96.3). D2 Values across the clusters ranged from 128.81 to 15699.76. The maximum inter-cluster distance was noticed between cluster X and cluster III (15699.76); followed by cluster X and cluster V (15568.61); cluster X and cluster VI (12020.02) and cluster X and cluster I (11083.56). Plant height (37.1%), number of pod clusters/plant (28.83%), total number of pods/plant (21.48%) and number of nods/plant (5.95%) contributed the most to diversity. Genotypes included in Cluster X & Cluster III; Cluster X & Cluster V and Cluster X & Cluster VI were identified for diverse source in the hybridization programme for identification of desirable transgressive segregants for important Agronomic traits in soybean.